2021
DOI: 10.1177/21501327211041486
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, and Laboratory Predictors of In-Hospital Mortality Among COVID-19 Patients Admitted in a Tertiary COVID Dedicated Hospital, Northern India: A Retrospective Observational Study

Abstract: Introduction COVID-19 pandemic still poses a serious challenge to health system worldwide. This study was planned to determine exposure characteristics, in-hospital mortality, and predictors of in hospital mortality among COVID-19 patients. Material and methods We retrospectively investigated epidemiological, clinical, and laboratory profile of confirmed COVID-19 patients admitted from 25th March to 31st August 2020. COVID-19 patient profiles were collected from Medical Record Section of the hospital. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…According to large observational studies, the mortality of hospitalized COVID-19 patients declined from 30% in early-2020 to 15% in mid-2020 [ 79 ]. Observational studies in India, where many CAM studies were conducted, reported the mortality of hospitalized COVID-19 patients of 10% in mid-2020 [ 80 ]. Based on our meta-analysis, patients who developed CAM may present worse outcomes than the COVID-19 patients without CAM, although the causal relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…According to large observational studies, the mortality of hospitalized COVID-19 patients declined from 30% in early-2020 to 15% in mid-2020 [ 79 ]. Observational studies in India, where many CAM studies were conducted, reported the mortality of hospitalized COVID-19 patients of 10% in mid-2020 [ 80 ]. Based on our meta-analysis, patients who developed CAM may present worse outcomes than the COVID-19 patients without CAM, although the causal relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for mortality in COVID-19 reported in various studies included advanced age [ 2 13 ], male gender [ 6 , 7 , 9 , 11 , 13 ] and comorbidities [ 3 , 5 , 6 , 9 – 16 ] like diabetes mellitus, obesity, systemic hypertension, renal diseases, coronary artery disease [ 12 ] and malignancy. Apart from manifestations such as fever [ 8 ], cough [ 8 ], haemoptysis [ 2 ], dyspnoea [ 2 , 6 , 8 ], fatigue [ 8 ], loss of consciousness [ 2 , 6 ], laboratory parameters such as elevation of Neutrophil-to-Lymphocyte Ratio (NLR) [ 2 , 15 ], and increased levels of creatinine [ 3 ], lactate dehydrogenase (LDH) [ 2 4 , 10 , 12 ], direct bilirubin [ 2 ] and alanine aminotransferase [ 3 ], which provide early clues to the severity of disease, an increased plasma level of biomarkers like D-dimer [ 3 5 , 12 ], C-Reactive Protein (CRP) [ 6 , 7 ], serum ferritin [ 3 ], Interleukin-6 (IL-6) [ 3 ], and procalcitonin (PCT) fortifies these findings[ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed in a study in India and in a study in China also. 22,23 The association of CKD might be due to the fact that ACE2, the cell entry receptor of SAR-CoV-2 is expressed almost 100 times higher in the kidneys compared to lungs. 24…”
Section: Discussionmentioning
confidence: 99%